2008
DOI: 10.1007/s11340-008-9131-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Dynamic (Young’s and Shear) Moduli of a Structural Adhesive Using Modal Based Direct Model Updating Method

Abstract: In this paper, mechanical characteristics (Young's modulus and shear modulus) of an adhesive are identified using modal based direct model updating method and experimental modal data. The results show that both Young's and shear moduli of adhesive are frequency dependent. Also, it is demonstrated that the thickness and length of the adhesive-line have influence on these properties. All experiments and subsequent identifications are conducted both in bending and shear modes, and it has been shown that the shear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…They found that the bond length and the bottom thickness are dominant factors besides side width and top thickness. Jahani & Nobari (2008) demonstrated that both Young's and shear moduli of adhesive are frequency dependent in dynamic testing because adhesive materials show viscoelastic behaviour.…”
Section: Strain Transferring Mechanism For Surface-bonded Ofssmentioning
confidence: 99%
“…They found that the bond length and the bottom thickness are dominant factors besides side width and top thickness. Jahani & Nobari (2008) demonstrated that both Young's and shear moduli of adhesive are frequency dependent in dynamic testing because adhesive materials show viscoelastic behaviour.…”
Section: Strain Transferring Mechanism For Surface-bonded Ofssmentioning
confidence: 99%
“…Thus, frequency-time interconversion methods are valuable and useful tools (Emri and von Bernstorff 2005;Schapery 1999a, 1999b) due to the fact that they can also be applied to overcome the inherent difficulties of relaxation or dynamic characterizations (Kulik et al 2009;Maheri and Adams 2002;Jahani and Nobari 2008), depending on the tested material. The most widely applied methods (Emri and von Bernstorff 2005) for material functions conversion from time to frequency domains are those based on Prony series (Chen 2000), and the opposed conversion can be achieved through the algorithms proposed by Ninomiya and Ferry (1959).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the methods proposed by Schwarzl (1970) should be highlighted also since both interconversions can be achieved. More recently, other authors have proposed other methods (Emri and von Bernstorff 2005;Schapery 1999a, 1999b;Kulik et al 2009;Maheri and Adams 2002;Jahani and Nobari 2008;Chen 2000;Ninomiya and Ferry 1959;Fernández et al 2011;Schwarzl 1970;Sorvari and Malinen 2007). Nevertheless, that of Leblanc (2005) should be highlighted, as his work focuses on the employment of the Fourier transform but in order to investigate non-linear viscoelastic materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first types are tensile tests which are static or low frequency tests. The second types are resonant tests which can predict wide frequency range characteristics of the material [2].…”
Section: Introductionmentioning
confidence: 99%